Integrated reliability assessment of medium voltage networks incorporating voltage and reactive power performance indices - Dewan Ashikur Rahaman; Md. Minhaj Pathan; Aive Alamgir; Md. Masum Howlader; Kazi Mahtab Kadir; Md. Shazzad Dewan; Md. Yakub Hassan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2026)
Energy system operation relies on synchronous protection and safety, with stable networks able to handle disruptions without abrupt changes. Due to the complexity of modern electrical systems, contingency analysis is essential for addressing issues in power system analysis. This study presents a comprehensive method for identifying the initial causes of cascading system failures in power systems. Case studies utilizing IEEE test systems with various cascade models demonstrate the effectiveness of this approach. The analysis aids in evaluating the possible impacts on the system and informs preventive strategies to avoid failures. This study integrates voltage stability and reactive power performance indices to create a framework for assessing the reliability of a medium-voltage power network operating at 33 kV. It evaluates N-1 and N-2 contingencies due to line and generator outages to identify and rank critical network components. In contrast to traditional reliability evaluations, the approach identifies weaknesses connected to voltage that impact system resilience. The proposed approach enables improved ranking of severe contingencies beyond conventional methods, supporting targeted reinforcement and enhancing voltage stability and overall system reliability.